(untitled) (REMUNOM, 2024)
As we know, we are experiencing an intense and never-ending institutional crisis here. This crisis creates extreme burdens for ordinary citizens who are unable to save, invest and, therefore, are unable to prosper, a relationship closely linked to the spread of poverty. In the world there is a clear difference between developed and underdeveloped countries, those that ended poverty and those that let it flow. The important task is to discover what was done to achieve this. There is an almost crony relationship between economic freedom and the eradication of poverty. The Heritage Foundation Institute shows this relationship clearly, being the main world census in measuring economic freedom, applying scores from 0 to 100 according to the level of freedom, with those closest to 0 being the poorest and those closest to 100 being the richest, that is, the higher As we know, we are experiencing an intense and never-ending institutional crisis here. This crisis creates extreme burdens for ordinary citizens who are unable to save, invest and, therefore, are unable to prosper, a relationship closely linked to the spread of poverty. In the world there is a clear difference between developed and underdeveloped countries, those that ended poverty and those that let it flow. The important task is to discover what was done to achieve this. There is an almost crony relationship between economic freedom and the eradication of poverty. The Heritage Foundation Institute shows this relationship clearly, being the main world census in measuring economic freedom, applying scores from 0 to 100 according to the level of freedom, with those closest to 0 being the poorest and those closest to 100 being the richest, that is, the greater the freedom, the greater the wealth. Another clear relationship shown by this institute is the ratio established between political stability and economic freedom, which is the fundamental basis for the eradication of poverty. These two things that are not present in underdeveloped countries, which for the most part live from crisis to crisis, from coup to coup, never achieving the rule of law, economic freedom, the preservation of individual guarantees, and consequently, never managing to abolish once and for all, poverty. The Brazilian Constitution of 1988, currently in force, is the cradle of political-economic instability.